PEMODELAN SIMULASI PRODUKSI BAKSO DAN SISTEM DISTRIBUSI - Risky Agung Nurdian; Rensa Prasidyajyandalu; Moch. Bagoes Ali Masyhuri; Dwi Rolliawati (UPPM Politeknik Gorontalo, 2020)
Intense competition at the present time requires producers to increase the effectiveness and efficiency of human resources and product material resources. Meatball X production is one of the small industrial productions engaged in the culinary field. In the production process and distribution of meatball X production is still not optimal. This study aims to make simulation modeling to maximize production and distribution in meatball X production. The results of the research of the meatball manufacturing process go through 4 stages namely milling, emulsification, printing, and packaging. With a total production of 1200 pieces per day and produces a maximum income of Rp. 1,800,000 with a net profit of Rp. 1,025,000. To determine the shortest route and distribution path using the Dijkstra algorithm. From the Dijkstra calculation results the shortest route and path as far as 14.1 Km with this route X meatball production can shorten the distribution time and reduce costs for fuel.